Optimization of Data Security System Control with CRC (Cyclic Redundancy Check) Algorithm - Purwanto, Dedi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Authenticity is one of the critical factors in data communication; moreover, making a program implementation design tasked with data security is one solution to determine the authenticity of the data. This application system is designed using Microsoft Visual Studio 2010, WampServer 5.0, ODBC Connector 5.3. This application system is built using the CRC (Cyclic Redundancy Check) algorithm to determine the file's checksum. Thus, the author hopes that the user can find out whether the received file has been modified in the transmission process. to avoid access by unauthorized parties. The method of sending data often has the risk of unwanted changes to the data.